Mobile-Based Spatial Map Application of Horticulture Produce in Wonosalam Sub District, Jombang District, East Java - Irfianti, A. D.; Widiwurjani; I. Y. Purbasari; A. Hendi (Nusantara Science and Technology Proceedings)
The purpose of this study is to build information on spatial maps (Geographic Information System-GIS) on horticulture commodities. Users of the Mobile GIS (MoGIS) application are observers of agricultural issues, agricultural services, industrial institutions, professionals related to agricultural problems from upstream to downstream. This moGIS is expected to help every region that has superior products of horticultural crops, where its data will be integrated with moGIS with the compass traveler technique that becomes the system of a region on the map. The specific target in this study is to present horticulture information in the sub-district of Wonosalam, Jombang, East Java by using moGIS. If each horticultural data of each region can be integrated with moGIS, users will know the potential of superior crops in the area which is expected to improve production and better quality, thus making the region and its produce are growing and better known by the community. The activity plan in developing this model are: (1) Analysis of the need for research equipment and survey data on locations, while data collection includes horticultural data and land photo data so that plants that have grown and developed in the area can be identified, (2) Mobile spatial-based system designs which includes the user interface and performance of the data system and interface, (3) coding and system data, (4) trial and (5) Maintenance or improvement to expand the data system. The result is a working app in beta version available for download in the Android marketplace.